Investigations on chitin and coconut fiber reinforcements on mechanical and moisture absorption properties of corn starch bioplastics. (2022) - Pradeep, Manu; Binoy, Rahul Francis; Yaswanth, S.; Pullan, Thankachan T.; Joseph, Mathew
Highlights: Synthesis of corn starch based bioplastics with scope in food packaging is studied. Chitin and coconut fibres are used as reinforcements in corn starch matrix. Tensile strength, water absorption and percentage elongation was studied for bioplastics by varying plasticizer content. Coconut fibre and chitin can improve moisture absorption, tensile strength and elongation flexibility of corn starch bioplastics. Abstract: Plastic garbage stacking up in landfills poses a severe environmental danger. Bioplastic manufactured from several biodegradable materials is one approach for reducing such problems. In this work, corn starch bioplastic (BP) was prepared by gelatinization. The BP was reinforced with 10 wt% chitin as wells as 10 wt% coconut fibers to obtain chitin reinforced bioplastic (CH-BP) and coconut fiber reinforced bioplastic (CF-BP). The chitin was extracted from shrimp cells. SEM and XRD characterization of chitin extracted were conducted to study the fiber formation and structure. The effect of plasticizer glycerol on the tensile strength, elongation, and moisture absorption, were compared for BP, CH-BP and CF-BP. The increase in glycerol content increased the elongation, flexibility and moisture absorption for all the three types of bioplastics, however, the tensile strength decreased. The tensile strength of CF-BP was slightly more at various glycerol concentration, whereas, the elongation percentage and moisture absorption was low compared to CH-BP and BP. The CF-BP can be employed for applications that requires more strength, the CH-BP in applications that require flexibility and BP where high moisture absorption is necessary. Nevertheless, the concentration of fillers and glycerol should be optimized for various applications.